Prognostic Factors of Functional Recovery from Left Hemispheric Stroke - Siriphan Kongsawasdi; Jakkrit Klaphajone; Kanokwan Watcharasaksilp; Pakorn Wivatvongvana (The Scientific World Journal)
Although lateralization of the brain affects some specialized cortical functions, there are still limited data to address its influence on clinically important outcomes. This study aimed to reveal the prognostic variables that relate to functional recovery in stroke patients with a left-sided hemispheric lesion during 6 months of follow-up. Data from 167 left-sided and 183 right-sided hemispheric strokes were reviewed retrospectively. Outcomes in this study included walking capacity and functional recovery, assessed by the modified Rankin Scale (mRS). In order to obtain independent predictive variables, this study used the step-backward method of multivariable regression analysis of parameters. The final model demonstrated that motor function of the hemiparetic leg was the strongest independent predictor for both walking ability and functional recovery (risk ratio (RR) of 2.41, 95% CI: 1.61–3.60, and p<0.001 and RR of 1.83, 95% CI: 1.03–3.26, and p=0.04, resp.). Therefore, lateralization did not seem to be involved. Understanding predictable variables that are associated with recovery can guide the rehabilitation team in setting priority and appropriate treatment for stroke patients.